1982
DOI: 10.1007/bf00256525
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fertility after testicular torsion: An experimental study

Abstract: The spermatic cord was ligated in Charles River adult rats producing viable reversible and non viable damaged testes. Weight of the rats, weight of the testes, weight of the epididymis, sperm motility, sperm concentration and fertility were the different parameters assessed. The results showed that there is a high percentage of subsequent atrophy in the ligated testes, and that there is a definite correlation between the length of the occlusion and the amount of testicular injury sustained. Leaving a ligated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Nagler and White [7], Nagler et al [8], and Merimsky et al [6] reported that unilateral testicular torsion in mature rats results in contralateral testicular damage consisting of distorted tubular architecture, decreased seminiferous tubular diameter, and no sperm cells within the tubular lumen [7,81. These authors and others [3] believe that this phenomenon appears to be immunologically mediated and can be prevented by early orchiectomy of the infarcted testis or by splenectomy plus antilymphocytic globulin.…”
Section: Discussionmentioning
confidence: 99%
“…Nagler and White [7], Nagler et al [8], and Merimsky et al [6] reported that unilateral testicular torsion in mature rats results in contralateral testicular damage consisting of distorted tubular architecture, decreased seminiferous tubular diameter, and no sperm cells within the tubular lumen [7,81. These authors and others [3] believe that this phenomenon appears to be immunologically mediated and can be prevented by early orchiectomy of the infarcted testis or by splenectomy plus antilymphocytic globulin.…”
Section: Discussionmentioning
confidence: 99%
“…groups studied, even in the control study, although in a lower degree. Merimsky et al [4] found that 4 rats in their study already had antibodies before the experimental study was performed. For some authors [17,18], includ ing those who support this hypothesis, the mere manipu lation of the testicle even with no ischemia is enough to result in an immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that testicular torsion affects the contralateral testis, as reflected by reduced DNA flow cytometric evaluation is obtained in about 80% of gonads aspirated [13]. Testicular tissue is suitable contralateral testicular blood flow, significant morphological changes, impaired fertility and sperm motility, as for analysis by DNA flow cytometry because it is composed of several cell populations at various stages of well as by alterations in the DNA histograms obtained by DNA flow cytometry [2][3][4][5][6]. Other authors argue that development, with distinctly different quantities of DNA.…”
mentioning
confidence: 99%